Nutritional Compositions and Sensory Evaluation of Fermented Maize and Millet Fortified with Crayfish and Soybeans for the Production of Infant Food - Mosunmola Aderonke Ilemobayo; Kikelomo Jennifer Kone (AgriHealth: Journal of Agri-food, Nutrition and Public Health, 2024)
Despite the reported improvement in the nutrient status of fermented cereal-based diets in Sub-Saharan Africa, the nutrient needs of infants are still not being met. Hence, this study evaluated the nutritional compositions of fermented protein-fortified cereals. The proteins used in fortifying maize and millet were crayfish (30%), soybeans (30%) and a combination of both protein sources in a ratio of 70:15:15 for cereals, crayfish and soybeans, respectively. Fermentation of protein-fortified cereals was carried out using submerged fermentation for 5 days. Results revealed that fortifying maize and millet with crayfish and soybeans increased the protein content (11.1 to 19.1%). The fortification led to a reduction in crude fiber and carbohydrate contents of raw maize and millet. Fermentation also significantly reduced the carbohydrate content, with the lowest carbohydrate value observed on the last day of fermentation. Fortification with crayfish and fermentation increased all the minerals (potassium, magnesium and calcium) of raw maize and millet, but no significant effect at p < 0.05 on the iron content. All the samples that were fortified had better sensory acceptability than those that were not fortified. This study revealed that fermentation and fortification of maize and millet meal (cereal) with soybeans and crayfish can alleviate protein energy malnutrition (PEM) problems.